2018
DOI: 10.3126/jns.v5i0.19495
|View full text |Cite
|
Sign up to set email alerts
|

Action Research on Improving Students' Speaking Proficiency in Using Cooperative Storytelling Strategy

Abstract: Speaking is the first way to interact with others in the social community. Furthermore, the success in learning a language at first can be seen from the ability of the learner’s speaking. However, it is very hard for the second language learners to speak the foreign language, especially English. There are a lot of reasons why they get difficulties in speaking, such as lack of ideas to tell, lack of vocabularies to express the ideas, lack of the exposure to speak, and lack of the interesting teaching method or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 1 publication
0
19
0
Order By: Relevance
“…The Concept of Cooperative Learning Process(https://nadajaffal.info, 2020) Lecturer as a developer of lesson plan (RPP) need to have an adequate understanding of the learning models so that its implementation in appropriate learning and learning objectives can be achieved effectively. But in reality there are lecturers who only use conventional learning models by using the lecture method that causes a passive student who does not comply with the current educational paradigm that is student centered, based on active learning (Sharma, 2018).…”
Section: Figurementioning
confidence: 99%
“…The Concept of Cooperative Learning Process(https://nadajaffal.info, 2020) Lecturer as a developer of lesson plan (RPP) need to have an adequate understanding of the learning models so that its implementation in appropriate learning and learning objectives can be achieved effectively. But in reality there are lecturers who only use conventional learning models by using the lecture method that causes a passive student who does not comply with the current educational paradigm that is student centered, based on active learning (Sharma, 2018).…”
Section: Figurementioning
confidence: 99%
“…Studies have shown that, if opportunities are not provided for social interaction, learners may be deprived of the opportunity to express their thoughts and opinions, as well as the opportunity to improve their fluency and confidence (Fauzan, 2016;Friesen & Haigh, 2017;Raba, 2017;Sharma, 2018). Learners need to practise English and use it communicatively inside and outside the classroom.…”
Section: Theme 3: Cip Interactive Activitiesmentioning
confidence: 99%
“…Storytelling is not limited to entertainment but also used as an effective teaching tool in a language classroom (Mokhtar, Halim, & Kamarulzaman, 2011). The students can improve their speaking proficiency and motivation by using storytelling techniques (Sharma, 2018). The shy students can start to speak English in the classroom.…”
Section: Improving Speaking Skillsmentioning
confidence: 99%